Specefic form of short-term financing - Suzana Baresa; Sinisa Bogdan; Zoran Ivanovic (UTMS Journal of Economics, 2017)
The aim of this paper is to point out the significance and role of factoring as an alternative financing model, and its role in overcoming liquidity problems of business entities due to difficult and late payments as well as long-term billing. Businesses face the challenge of addressing liquidity-related financial difficulties, particularly in the context of dynamic business overruns, financial and economic instability and uncertainty, and difficulties associated with the impossibility of obtaining financial resources. Therefore, this paper examines the significance and role of factoring, through an overview of relevant literature and examples from the business world. The importance of factoring is discussed as an opportunity to overcome the problem of liquidity of business entities and as a model of financing, especially for small and medium-sized enterprises. The paper summarizes the overall effects of factoring, as well as the stated traps of its use. It is not good for businesses to rely solely on credits due to inability to raise funds because it hampers their development and market competitiveness.
Keywords: G32; G29; 330; Factoring; liquidity; solvency; receivables; Croatia